Traumatic progression: psychoanalytic and neuroscientific dimensions. Issue 1 (3rd July 2021) - Miller, Christopher W. T.
ABSTRACT: Advances in neuroscience have promoted greater interdisciplinary dialogues, including with psychoanalytic theories. The concept of premature development in response to childhood experiences of abuse has been developed by analysts including Sándor Ferenczi and Sigmund Freud. Such traumatic events lead a child to hasten psychic and somatic development in accordance with destructive and confusing impingements from the environment. Aligned with these theories, neuroscientific investigation has demonstrated comparable effects resulting from childhood trauma, including an accelerated and incomplete development of neural circuitry, as well as a physiological maturation that lowers the age of reproductive availability. These biological consequences, in conjunction with the effects of early trauma on later behaviors, including impulsivity and sexual risk-taking, may increase chances of early conception, which authors have posited may be an evolutionary adaptation to a chaotic environment. In addition, epigenetic and endocrine markers may be passed on by traumatized individuals to their offspring, potentially predisposing the latter to greater physiological stress in-utero and during early life, potentially furthering intergenerational effect of trauma. By combining insights from biological and psychoanalytic arenas, an enriched understanding can emerge from which to investigate the manifold effects of traumatic events, as relevant a concern today as it was a century ago.